Traditionally used wild edible plants of district Udhampur, J&K, India - Harpreet Bhatia; Yash Pal Sharma; R. K. Manhas; Kewal Kumar (BMC, 2018)
Abstract Background Wild edible plants (WEPs) refer to edible species that are not cultivated or domesticated. WEPs have an important role to play in poverty eradication, security of food availability, diversification of agriculture, generation of income resources, and alleviating malnutrition. In the present study, an inventory of traditionally used WEPs from Udhampur district of J&K, India, has been prepared. Methods A systematic and extensive ethnobotanical survey was carried out in different villages of the district for the collection of information on WEPs. The data collected through questionnaire and interviews was then analyzed for cultural importance index (CI) and factor informant consensus (F ic) to know the cultural significance of WEPs and consensus for the knowledge of WEPs among the informants. Results A total of 90 plant species belonging to 45 families and 78 genera were edible and serve as wild phytofoods in the present study. Species richness of wild edible species was the maximum for vegetables (46 species) followed by fruits (37 species) and medicinal plants (36 species). Culturally (on the basis of CI), the most important vegetable and fruit species were Diplazium esculentum, Fumaria indica, Taraxacum campylodes, Urtica dioica, Phyllanthus emblica, Punica granatum, Cordia dichotoma, Syzygium cumini, Ficus palmata, etc. The highest use-report (626) was recorded for vegetables whereas the maximum mean use-report (14.8) was recorded for fruits. On an average, 20.7 wild edible species were used per informant. Informant consensus index (F ic) varied between 0.83 and 0.94 for raw vegetables and preserved vegetables, respectively. Conclusion One of the most important issues of this era is hunger for which one of the possible solutions is the usage of WEPs. The local populace of Udhampur has good knowledge of WEPs, and this legacy of traditional culture must be conserved.